2017
DOI: 10.1186/s12943-017-0653-4
|View full text |Cite
|
Sign up to set email alerts
|

Human germ/stem cell-specific gene TEX19 influences cancer cell proliferation and cancer prognosis

Abstract: BackgroundCancer/testis (CT) genes have expression normally restricted to the testis, but become activated during oncogenesis, so they have excellent potential as cancer-specific biomarkers. Evidence is starting to emerge to indicate that they also provide function(s) in the oncogenic programme. Human TEX19 is a recently identified CT gene, but a functional role for TEX19 in cancer has not yet been defined.MethodssiRNA was used to deplete TEX19 levels in various cancer cell lines. This was extended using shRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…Recent work in mice has demonstrated that the mammalian-specific gene Tex19.1 is required to promote normal levels of these meiotic recombination-initiating events (49). The human ortholog, TEX19, normally has expression restricted to the testis and embryo stem cells, but is also widely activated in cancer cells (31); importantly, this expression is required in a number of distinct cancer cell types to mediate proliferation and cancer stem-like cell self-renewal (50). While the mechanism of action of TEX19 in cancer cells remains unknown, this work further demonstrates the functional requirements for diverse meiotic chromosomal modulators, including regulators of meiotic recombination initiation, in oncogenesis.…”
Section: Activation Of Meiotic Functions In Cancer Cellsmentioning
confidence: 99%
“…Recent work in mice has demonstrated that the mammalian-specific gene Tex19.1 is required to promote normal levels of these meiotic recombination-initiating events (49). The human ortholog, TEX19, normally has expression restricted to the testis and embryo stem cells, but is also widely activated in cancer cells (31); importantly, this expression is required in a number of distinct cancer cell types to mediate proliferation and cancer stem-like cell self-renewal (50). While the mechanism of action of TEX19 in cancer cells remains unknown, this work further demonstrates the functional requirements for diverse meiotic chromosomal modulators, including regulators of meiotic recombination initiation, in oncogenesis.…”
Section: Activation Of Meiotic Functions In Cancer Cellsmentioning
confidence: 99%
“…Although the Tex19.1 −/− phenotype indicates that Tex19.1 plays a role in maintaining arm cohesion in oocytes, the biochemical function of TEX19.1 is poorly understood. Both mouse Tex19.1 and human TEX19 are functional in some nonmeiotic somatic cell types that naturally express these genes ( Reichmann et al, 2013 ; Tarabay et al, 2013 ; Planells-Palop et al, 2017 ). Therefore, to investigate whether the ability of mouse Tex19.1 to regulate sister chromatid cohesion is conserved in human TEX19 and extends from meiosis to mitosis, we expressed human TEX19 in human HEK293T cells that do not normally express this gene ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tex19.1 is a member of the mammal-specific family of TEX19 genes that duplicated during rodent evolution ( Kuntz et al, 2008 ). Mouse Tex19.1 is syntenic with human TEX19 , and these genes appear to have similar expression patterns in pluripotent cells and in fetal and postnatal male and female germ cells ( Öllinger et al, 2008 ; Kuntz et al, 2008 ; Hackett et al, 2012 ; Planells-Palop et al, 2017 ). Tex19.2 is expressed in somatic cells in the testis and at more restricted stages of gametogenesis ( Kuntz et al, 2008 ; Celebi et al, 2012 ; Hackett et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, another CT gene involved in SPO11‐mediated recombination regulation in mammals, TEX19 , has been reported to be required for maintaining the proliferative state of cancer cells (Planells‐Palop et al ., ). The functional nature of human TEX19 in cancer cells remains unknown, but the TEX19 gene appears to be extensively activated in a range of cancer type (Feichtinger et al ., ; Zhong et al ., ).…”
Section: Activation Of Meiotic Chromosome Regulators In Non‐germ Cellmentioning
confidence: 97%
“…Murine Tex19.1 appears to regulate a number of germ line biological functions, most likely via a defined association with the murine Ubr2 E3 ubiquitin ligase, and these include regulation of LINE1 transposition and the initiation of SPO11 meiotic recombination (Yang et al ., ; Reichmann et al ., ; Tarabay et al ., ; Crichton et al ., , ; MacLennan et al ., ). TEX19 is mammalian‐specific and so the D. melanogaster l(3)mbt tumour studies do not shed any light on whether TEX19 is required early in the oncogenic programme, as well as being required to maintain the proliferative status of cancer cells, although preliminary analysis of human tumour progression arrays suggests that it is activated early in the oncogenic programme (Planells‐Palop et al ., ).…”
Section: Activation Of Meiotic Chromosome Regulators In Non‐germ Cellmentioning
confidence: 97%